Anaerobic Biodegradation of Raw and Pre-treated Brewery Spent Grain Utilizing Solid State Anaerobic Digestion - Panjičko, Mario; Zupančič, Gregor Drago; Zelić, Bruno (Acta chimica Slovenica, 2015)
The brewery spent grain (BSG) represents approximately 85% of the total quantity of by-products from the brewing industry. The biogas production from the BSG has been the subject of several studies in recent years, due to relatively high energy consumption in the brewing process and due to the increasing energy costs. The biodegradability of raw and pre-treated BSG in a single-stage and two-stage solid-state anaerobic digestion (SS-AD) system was determined in this study. The results show that the BSG have a biogas potential of 120 L/kg(-1). In the single-stage system, the biogas yield obtained from raw BSG (87.4 L/kg(-1)) was almost equal to the yield obtained from the pre-treated BSG (89.1 L/kg(-1)), while the methane yield was 51.9 and 55.3 L/kg(-1) and the biodegradation was 62.0% and 62.2% for raw and pre-treated BSG, respectively. In two-stage SS-AD the pre-treated BSG showed better results, with the biogas yield of 103.2 L/kg(-1) and the biodegradation of 73.6%, while the biogas yield obtained from raw BSG was 89.1 L/kg(-1), with the biodegradation of 63.5%. In two-stage process the obtained methane yields from raw and pre-treated BSG were identical (58.7 L/kg(-1)).